Implementasi Strategi Pembelajaran Kontekstual dalam Pendidikan Agama Islam untuk Membentuk Karakter Siswa - Dimas Agustian Vieri S; Firza Ulul Azmi; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the implementation of contextual learning strategies in Islamic Religious Education (PAI) to build student character. The method used is library research with a qualitative approach, analyzing various literature related to contextual learning and character building within the context of PAI. The findings show that contextual learning positively impacts students' awareness of the importance of Islamic values applied in daily life. Through this approach, students are able to connect theory with practice, strengthen their moral and social attitudes, and build character in accordance with Islamic teachings. The implementation of contextual learning also encourages students to become more active, reflective, and responsible in living a religious life. This research contributes to the development of more relevant and experience-based religious education.